Geodeics on the coset spaces as a dynamical realization of l-conformal Galilei algebra; Перспективы развития фундаментальных наук; Т. 3 : Математика - Chernyavsky D. V. Dmitry Viktorovich (2017, 2017)
Заглавие с экрана